Internet-Connected Gamefowl Feed Control System with Weight Sensor - Alimin, Alimin; Aqla, Kariman (Journal of Electrical Engineering and Computer (JEECOM), 2026)
This study presents the design and implementation of an Internet of Things (IoT)–based feed control system for gamefowl (fighting chickens) to ensure consistent rations when the breeder is away. The system combines a load cell with an HX711 weight-sensor interface to measure dispensed feed, an Arduino Uno microcontroller to execute control logic, and an ESP8266 Wi-Fi module to exchange data with a cloud service. An Android application allows users to set the target feed mass in grams, start or stop dispensing, and monitor real-time weight feedback. A prototype development method was applied, covering requirement elicitation, hardware and software design, implementation, and functional testing. Performance was evaluated through 20 dispensing trials using a 10 g tolerance limit derived from breeder practice. The prototype achieved successful dosing in all trials, with measured outputs remaining within the defined tolerance and providing immediate feedback to the mobile interface. The results indicate that the proposed system can automate portioning, reduce the risk of overfeeding or underfeeding, and support remote feed management for small-scale poultry operations.